Validating the total illness burden index for prostate cancer (TIBI-CaP) in men with castration-resistant prostate cancer: data from TRUMPET. (8th February 2018) - Flanders, Scott C; Kim, Janet; Wilson, Samuel; Braziunas, Jeffrey; Greenfield, Sheldon; Billimek, John; Lechpammer, Stanislav; Lin, Daniel W; Karsh, Lawrence; Quinn, David I; Shevrin, Daniel; Shore, Neal D; et al.
Aim: To validate the total illness burden index for prostate cancer (TIBI-CaP) in castration-resistant prostate cancer (CRPC) patients.Patients & methods: Baseline comorbidity scores collected using the TIBI-CaP were compared with the baseline patient-reported health-related quality of life using the SF-12v2 and FACT-P questionnaires in 302 patients enrolled in the Treatment Registry for Outcomes in CRPC Patients (TRUMPET).Results: Baseline TIBI-CaP scores were negatively correlated with all baseline SF-12v2 domain/composite (p < 0.001) and FACT-P subscale/total (p < 0.020) scores. There was a significant decreasing linear trend in SF12v2 and FACT-P scores over the categories based on TIBI-CaP quartiles of comorbidity burden (from 'least' to 'severe').Conclusion: The TIBI-CaP is a valid measure of comorbidity burden in patients with CRPC in the real world. Lay abstract: This study aimed to validate the total illness burden index for prostate cancer (TIBI-CaP), a patient-reported measure of comorbidity burden, in a cohort of men enrolled in the Treatment Registry for Outcomes in Castration-resistant Prostate Cancer (CRPC) Patients (TRUMPET). Results from this study demonstrate that the TIBI-CaP is a valid measure of comorbidity burden in CRPC patients in the real world and a useful research tool for risk adjustment in CRPC studies.